2017
DOI: 10.1038/s41598-017-16056-3
|View full text |Cite
|
Sign up to set email alerts
|

Histological evidence for a dynamic dental battery in hadrosaurid dinosaurs

Abstract: The first histological study of an entire hadrosaurid dental battery provides a comprehensive look at tooth movement within this complex structure. Previous studies have focused on isolated teeth, or in-situ batteries, but this is the first study to examine an entire dental battery of any dinosaur. The absence of direct tooth-to-tooth contact across the entire battery and a unique arrangement of the dental tissues in hadrosaurids led us to compare their teeth with the ever-growing incisors of mammals. The simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…The enamel in Chengchunsaurus teeth is between 30 and 55 μm thick in erupting, unworn replacement teeth (and thus the closest approximation for maximum enamel thickness). In thin section, the enamel cap is the same thickness and roughly symmetrical on the labial and lingual sides of the tooth, unlike the condition in hadrosaurid and ceratopsid dinosaurs [ 2 , 6 , 8 , 9 , 13 , 29 ]. One thin section revealed that the labial face of the developing tooth crown may have a slightly shorter enamel-covered portion compared to that along the lingual surface, however the difference is subtle ( Fig 3F ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The enamel in Chengchunsaurus teeth is between 30 and 55 μm thick in erupting, unworn replacement teeth (and thus the closest approximation for maximum enamel thickness). In thin section, the enamel cap is the same thickness and roughly symmetrical on the labial and lingual sides of the tooth, unlike the condition in hadrosaurid and ceratopsid dinosaurs [ 2 , 6 , 8 , 9 , 13 , 29 ]. One thin section revealed that the labial face of the developing tooth crown may have a slightly shorter enamel-covered portion compared to that along the lingual surface, however the difference is subtle ( Fig 3F ).…”
Section: Resultsmentioning
confidence: 99%
“…In section, every tooth root is separated from the surrounding socket bone by a mineral-filled space. In modern crocodilians, this space houses the periodontal ligament in life [ 6 , 45 47 ]: a network of collagen fiber bundles that anchor into the walls of the tooth socket and the surface of the tooth root. The surfaces of the tooth roots in Changchunsaurus parvus are coated in a thin band of acellular cementum, and a thicker, outer layer of cellular cementum ( Fig 6 ), which would have been the anchoring points for the periodontal ligament [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations